Answer:
c=1
Step-by-step explanation:
Simplifying
3 + 2c = 5
Solving
3 + 2c = 5
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + 2c = 5 + -3
Combine like terms: 3 + -3 = 0
0 + 2c = 5 + -3
2c = 5 + -3
Combine like terms: 5 + -3 = 2
2c = 2
Divide each side by '2'.
c = 1
Simplifying
c = 1
Answer:
= 4
Step-by-step explanation:
Subtract 15 from both sides of the equation
6+15=39
6+15−15=39 − 5
Simplify
6=24
Divide both sides of the equation by the same term
(6=24)/6
Simplify
=4